Off-centered leadership : - Calagione, Sam (John Wiley and Sons, 2016)
Calagione considers an innovative approach to business by exploring what happens when companies stop competing and start collaborating-- both externally in the marketplace and internally in building a culture of communication, trust and alignment. Members of the leadership team at Dogfish Head Craft Brewery, as well as external mentors from the worlds of business and art, showcase how competing organizations can work together to reach a common goal.